2022
DOI: 10.1021/acs.jpca.1c10754
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bond Topology Is More Important Than Acid/Base Strength in Atmospheric Prenucleation Clusters

Abstract: We explored the hypothesis that on the nanoscale level, acids and bases might exhibit different behavior than in bulk solution. Our study system consisted of sulfuric acid, formic acid, ammonia, and water. We calculated highly accurate Domain-based Local pair-Natural Orbital- Coupled-Cluster/Complete Basis Set (DLPNO-CCSD­(T)/CBS) energies on DFT geometries and used the resulting Gibbs free energies for cluster formation to compute the overall equilibrium constants for every possible cluster. The equilibrium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 104 publications
0
54
0
Order By: Relevance
“…In a similar manner, because of its high abundance, formic acid was recently shown to be the most efficient organic acid in enhancing MSA–MA cluster formation. 82 Furthermore, by studying small clusters consisting of sulfuric acid, formic acid, ammonia, and water, Harold et al 83 recently showed that formic acid is just as effective as ammonia in stabilizing the clusters. Hence, further studies on the role of nitric acid and formic acid in cluster formation is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar manner, because of its high abundance, formic acid was recently shown to be the most efficient organic acid in enhancing MSA–MA cluster formation. 82 Furthermore, by studying small clusters consisting of sulfuric acid, formic acid, ammonia, and water, Harold et al 83 recently showed that formic acid is just as effective as ammonia in stabilizing the clusters. Hence, further studies on the role of nitric acid and formic acid in cluster formation is warranted.…”
Section: Discussionmentioning
confidence: 99%
“… 84 Formic acid has furthermore been shown to be just as effective as ammonia in stabilizing small clusters containing sulfuric acid, formic acid, ammonia, and water. 85 Hence, further studies on the role of formic acid in cluster formation are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Clusters containing SA, FA, A, and W were previously optimized with the M08-HX functional and the MG3S basis set. 68,100 All of these M08-HX geometries were re-optimized with uB97X-D using the 6-31++G** basis set [103][104][105][106] to obtain a nal set of consistent geometries. The electronic energies of all structures within 8 kcal mol −1 of the uB97X-D global minimum for each system were recomputed using the domain-based local pair natural orbital coupled-cluster (DLPNO-CCSD(T)) method [107][108][109][110][111][112][113][114][115][116][117][118][119][120] with single, double, and semi-canonical perturbative triple excitations with three Dunning basis sets, cc-pVnZ (n ¼ D, T, Q), [121][122][123][124] using the ORCA 5.0.1 program.…”
Section: Methodsmentioning
confidence: 99%
“…Rasmussen et al (SA) 3 (W) n were both calculated using uB97X-D for the geometry optimizations and DLPNO-CCSD(T) for the single-point energy calculations while the Zhu et al (SA) 2 (acetic acid)(W) n system was calculated using PW91PW91 for both geometries and energies. Differences in these methodologies could explain the discrepancy for when ionization occurs in these systems, as quite oen the DLPNO-CCSD(T)/CBS minimum differs from the DFT minimum for atmospheric clusters 58,59,68. 3.5 Tetramers of three acids and one base…”
mentioning
confidence: 99%